Board characteristics and bank performance in India. Issue 2 (June 2018) - Abdul Gafoor, C.P.; Mariappan, V.; Thiyagarajan, S.
Abstract: Using a sample of 36 scheduled commercial banks in India during the period of 2001–2014, we explore the impact of board structure characteristics such as board size, independence and CEO duality on bank performance. We find significant relationship between board size and bank performance when the board size is between 6 and 9. We also find positive and significant relationship between board independence and bank performance. Further, we find that the number of board meetings and a larger number of financial experts on the board are important for bank performance. However, we find no significant improvement in bank performance when the role of CEO and chairman is separated.